Aplikasi Pencatatan Keuangan Berbasis Web - Yiyin Kabiyo; Tadjuddin Abdillah; Nikmasari Pakaya (Diffusion: Journal of Systems and Information Technology, 2021)
CV. Dua Putra Satu Putri (DPSP) is one of the CVs located in Gorontalo District, Limboto Sub-district, Polohungo Village. Cash in and cash out data recording is still currently done conventionally. Financial data is recorded in a daily journal, which will later be processed into daily work reports. In the recording process, errors often occur, which result in delays in the process of making other reports. In addition, searching for data takes a long time because there is no good grouping of financial data. Based on that problem, it is important for CV. Dua Putra Satu Putri (DPSP) to apply a computerized accounting information system that functions to support the smooth running of business processes, improve the quality of reports, and also as the first step towards changes to the old system used by CV. Dua Putra Satu Putri (DPSP). This study aims to facilitate heavy equipment owners in the financial chart in the payment process for heavy equipment rental services at CV. Dua Putra Satu Putri (DPSP). The owner no longer recaps data in a handwritten manner, thus simplifying the process of managing financial data and making it easier for the owner to get a financial report result faster. The system development method used is the Prototype method by using the PHP programming language and MySQL database.